The psychology of sports media and the content of the media message in the sports field - amara, noureddine; h, Mohamed; صغيري رابح (sports creativity, 2025)
Sports media can achieve significant effects on individuals and sports institutions, making it a real social force. Many researchers believe that the greatest impact of sports media is modifying attitudes rather than interpreting them. It also works to strengthen and reinforce values, concepts, and behavioral patterns. Sports media is characterized by the spread and expansion of satellite broadcasting, which includes diverse channels that proliferate and compete. The media plays a guiding role in shaping and developing culture in all aspects of society's activities. In sports, the media is an important part of the process of creating awareness and raising the level of sports culture among the public to create positive relationships between individuals and society with sports activity as a social and cultural phenomenon linked to society. The style of media editing demonstrates the help that the editor provides to the public directly in reading, listening, and watching in conveying information, opinions, facts, and sports events. The journalist cannot invent miracles when using communication style, but he must understand the style well and correctly. The journalist should be like a teacher or instructor in terms of helping the public to understand it as well. The message of the sports media editor is considered the core of the editorial process, expressing the purpose and objectives of the source and sender, translating their opinions, aims, and desires into a symbolic form.